When Science Becomes Embroiled in Conflict: Recognizing the Public's Need for Debate while Combating Conspiracies and Misinformation. Issue 1 (March 2022) - Lewandowsky, Stephan; Armaos, Konstantinos; Bruns, Hendrik; Schmid, Philipp; Holford, Dawn Liu; Hahn, Ulrike; Al-Rawi, Ahmed; Sah, Sunita; Cook, John
We explore the common attributes of political conflicts in which scientific findings have a central role, using the COVID-19 pandemic as a case study, but also drawing on long-standing conflicts over climate change and vaccinations. We analyze situations in which the systematic spread of disinformation or conspiracy theories undermines public trust in the work of scientists and prevents policy from being informed by the best available evidence. We also examine instances in which public opposition to scientifically grounded policy arises from legitimate value judgments and lived experience. We argue for the public benefit of quick identification of politically motivated science denial, and inoculation of the public against its ill effects.